Presence of transplantable T-lymphoid cells in C57BL/6 mice infected with murine AIDS virus. - Kubo, Y (1992)
The Duplan strain of murine leukemia virus induces murine AIDS in C57BL/6 mice. When spleen cells from C57BL/6 mice infected with the virus were transplanted into nude mice, subcutaneous solid tumors at the transplanted sites were formed and splenomegaly and lymphadenopathy were induced. These transplantable cells were Thy-1- CD4+ alpha-beta T-cell receptor-positive T cells and integrated with the pathogenic defective viral genome. These results indicate that neoplastic cells of T-cell lineage were induced by infecting C57BL/6 mice with murine AIDS virus.